Pengaruh Faktor Karakteristik, Sikap dan Pengetahuan Dokter Terhadap Perilaku dalam Pengisian Rekam Medis di Poliklinik Rawat Jalan dan IGD Rumah Sakit Mitra Plumbon Cibitung Tahun 2024 - Andiwinata, Fauzi; Jamal, Jamal; Sukamdani, Nugroho B; Eddyono, Fauziah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to identify and analyze the influence of individual characteristics, attitudes and knowledge on the behavior of filling out medical records in the Outpatient Polyclinic and Emergency Room at Mitra Plumbon Cibitung Hospital. The research uses quantitative methods with a descriptive approach and analysis is carried out using SmartPLS. The results of the research show that individual characteristics, attitudes and knowledge each have a direct and significant influence on the behavior of filling out medical records in the Outpatient Polyclinic and Emergency Room at Mitra Plumbon Cibitung Hospital. Simultaneously, individual characteristics, attitudes and knowledge variables influence the behavior of filling out medical records with a contribution of 79.8%. However, individual experience and understanding of policies and procedures do not show a significant influence on the completeness and correctness of filling out medical records.